The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/cc10369
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function and Organ Dysfunctions in 178 Patients Requiring Mechanical Ventilation During The 2009 Influenza A (H1N1) Pandemic

Abstract: IntroductionMost cases of the 2009 influenza A (H1N1) infection are self-limited, but occasionally the disease evolves to a severe condition needing hospitalization. Here we describe the evolution of the respiratory compromise, ventilatory management and laboratory variables of patients with diffuse viral pneumonitis caused by pandemic 2009 influenza A (H1N1) admitted to the ICU.MethodThis was a multicenter, prospective inception cohort study including adult patients with acute respiratory failure requiring me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
4
37
0
1
Order By: Relevance
“…Another relevant data refers to the body mass index (BMI), which can be a risk factor for the development of various diseases, and also a signi icant factor to the worsening of the patient with the In luenza A virus (H1NI) (8). In the present research the data points to a high percentage, 81.81%, of patients with a BMI of ≥25kg/m².…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Another relevant data refers to the body mass index (BMI), which can be a risk factor for the development of various diseases, and also a signi icant factor to the worsening of the patient with the In luenza A virus (H1NI) (8). In the present research the data points to a high percentage, 81.81%, of patients with a BMI of ≥25kg/m².…”
Section: Discussionsupporting
confidence: 47%
“…In the more serious cases, survivors presented great bilateral pulmonary damage in 2 or more quadrants and signs of aveolar in iltrates with a substantial systemic in lammatory response, evidenced by radiography. These alterations had a great impact on oxygenation and induced severe pulmonary lesion (2,6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of published studies on NIV in pH1N1 is shown in table 2 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][36][37][38][39][40][41][42][43][44][45][46][47][48]. Of the 22 studies included in table 2, the majority were case series reports.…”
Section: Introductionmentioning
confidence: 99%
“…These included obesity, COPD, diabetes mellitus, asthma, immunosuppression, chronic kidney disease and heart failure [27][28][29][30]32]. The overall ICU mortality rate for critically ill cases of pH1N1 was close to 17% [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation